2020
DOI: 10.3390/nu13010048
|View full text |Cite
|
Sign up to set email alerts
|

[6S]-5-Methyltetrahydrofolic Acid and Folic Acid Pregnancy Diets Differentially Program Metabolic Phenotype and Hypothalamic Gene Expression of Wistar Rat Dams Post-Birth

Abstract: [6S]-5-methyltetrahydrofolic acid (MTHF) is a proposed replacement for folic acid (FA) in diets and prenatal supplements. This study compared the effects of these two forms on maternal metabolism and hypothalamic gene expression. Pregnant Wistar rats received an AIN-93G diet with recommended FA (1X, 2 mg/kg, control), 5X-FA or equimolar levels of MTHF. During lactation they received the control diet and then a high fat diet for 19-weeks post-weaning. Body weight, adiposity, food intake, energy expenditure, pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 79 publications
0
11
0
Order By: Relevance
“…Parameters investigated were concentrations of RBC folate (Pérez‐Conesa et al., 2009), PTF (Pérez‐Conesa et al., 2009; Tactacan et al., 2010), plasma 5‐MTHF (Pannia et al., 2021), egg folate (Tactacan et al., 2010), liver folate (Pérez‐Conesa et al., 2009; Tactacan et al., 2010) and liver 5‐MTHF (Pérez‐Conesa et al., 2009; Pannia et al., 2021).…”
Section: Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Parameters investigated were concentrations of RBC folate (Pérez‐Conesa et al., 2009), PTF (Pérez‐Conesa et al., 2009; Tactacan et al., 2010), plasma 5‐MTHF (Pannia et al., 2021), egg folate (Tactacan et al., 2010), liver folate (Pérez‐Conesa et al., 2009; Tactacan et al., 2010) and liver 5‐MTHF (Pérez‐Conesa et al., 2009; Pannia et al., 2021).…”
Section: Assessmentmentioning
confidence: 99%
“…2) (P érez-Conesa et al, 2009) and one in pregnant rats and assessed as having a high RoB (Tier 3)(Pannia et al, 2021). Two studies used an unspecified form of5-MTHF (P érez-Conesa et al, 2009;Tactacan et al, 2010) and one used CaLMF(Pannia et al, 2021). The number of animals per group ranged between 6 (P érez-Conesa et al, 2009) and 16-18(Pannia et al, 2021).Parameters investigated were concentrations of RBC folate(P érez-Conesa et al, 2009), PTF (P érez-Conesa et al, 2009;Tactacan et al, 2010), plasma 5-MTHF(Pannia et al, 2021), egg folate(Tactacan et al, 2010), liver folate(P érez-Conesa et al, 2009;Tactacan et al, 2010) and liver 5-MTHF (P érez-…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This also explains why the relationship between folate, B 12 , and GDM is more dependent on the genotype of rs1801131 ( Table 4 and Figure 2 ). More recently, an animal study indicated that dams that feed higher levels of 5-methyl-THF during pregnancy gained significantly more weight than dams that provide folic acid [ 40 ]. Their findings suggested that high-dose 5-methyl-THF exposure may play a role in the development of metabolic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Accepted manuscript 5-methyl-THF diets will increase the weight of the dams and their female offspring (35,36) .…”
Section: Accepted Manuscriptmentioning
confidence: 99%